A Cascade of Sequentially Expressed Sucrose Transporters in the Seed Coat and Endosperm Provides Nutrition for the Arabidopsis Embryo. Issue 3 (20th March 2015) - Chen, Li-Qing; Lin, I Winnie; Qu, Xiao-Qing; Sosso, Davide; McFarlane, Heather E.; Londoño, Alejandra; Samuels, A. Lacey; Frommer, Wolf B.
Abstract : Triple mutants of three sucrose-transporting SWEETs show reduced seed yield, indicating that multiple sucrose translocation pathways move sugar from the maternal to the filial tissues. Abstract: Developing plant embryos depend on nutrition from maternal tissues via the seed coat and endosperm, but the mechanisms that supply nutrients to plant embryos have remained elusive. Sucrose, the major transport form of carbohydrate in plants, is delivered via the phloem to the maternal seed coat and then secreted from the seed coat to feed the embryo. Here, we show that seed filling in Arabidopsis thaliana requires the three sucrose transporters SWEET11, 12, and 15. SWEET11, 12, and 15 exhibit specific spatiotemporal expression patterns in developing seeds, but only a sweet11;12;15 triple mutant showed severe seed defects, which include retarded embryo development, reduced seed weight, and reduced starch and lipid content, causing a "wrinkled" seed phenotype. In sweet11;12;15 triple mutants, starch accumulated in the seed coat but not the embryo, implicating SWEET-mediated sucrose efflux in the transfer of sugars from seed coat to embryo. This cascade of sequentially expressed SWEETs provides the feeding pathway for the plant embryo, an important feature for yield potential.